ΚΟΙΝΟΝ ΤΟΥ ΠΟΝΤΟΥ - Nawotka, Krzysztof (Balcanica Posnaniensia. Acta et studia, 1990)
The article addresses the problem of the date of the formation of the association of Greek cities on the western coast of the Black Sea (the koinon of Pontus). The problem is significant for studies on the administrative and political organization of Roman provinces. The aim of the work is to determine the chronology and composition of this assembly. The author applies analysis of epigraphic, numismatic, and literary sources. The most important results indicate that the koinon was established at the beginning of Trajan’s reign (AD 98–117), rather than earlier as previously assumed. It consisted of five main cities (including Tomis, Istria, and Kallatis), and at times also a sixth. The assembly had representative and religious functions, including those related to the imperial cult. The conclusion is that the koinon should be regarded as an institution formed within the framework of Roman administration, serving to integrate Greek poleis within the empire.